Verification of EMMS formulation using lattice Boltzmann simulations - Shah, Milinkumar; Utikar, Ranjeet; Tade, Moses; Pareek, Vishnu; Evans, G. (Elsevier, 2014)
Dilute gas solid flow in riser exhibits inherent heterogeneity due to the formation of clusters. Conventional drag models within continuum CFD simulations cannot adequately capture the clusters. The drag models have there-fore been modified using multi-scale approaches such as the energy minimization multi-scale (EMMS) model. The EMMS formulation needs to be critically evaluated before it can be confidently applied to simulate the riser flow. In this study, the EMMS model was verified by comparing the drag from the EMMS formulation with high resolution 3D lattice Boltzmann (LB) simulations. At cluster fraction higher than 0.3 and gas volume fraction lower than 0.9, the drag calculated by the EMMS model increases exponentially and gives unrealistic values for gas volume fraction lower than 0.86. Corrections to the equations for the drag forces in the EMMS formulation were suggested to overcome this anomaly. Calculated drag from the corrected EMMS model shows close agreement with the LB simulations over the entire range of the overall voidage, particle Reynolds number and multiple clusters. While finding cluster parameters at a given flow conditions needs cluster-scale experimental observations, this study verifies the formulation of the EMMS model paving the way to apply the EMMS model more confidently for dilute gas solid flow.